Total flavonoid extract of Epimedium herb increases the peak bone mass of young rats involving enhanced activation of the AC10/cAMP/PKA/CREB pathway. (15th September 2018) - Xi, Hui-Rong; Ma, Hui-Ping; Yang, Fang-Fang; Gao, Yu-Hai; Zhou, Jian; Wang, Yuan-Yuan; Li, Wen-Yuan; Xian, Cory J.; Chen, Ke-Ming
Abstract: Ethnopharmacological relevance: Epimedium sagittatum brevicornum Maxim. is an important traditional Chinese herb that has long been used to promote bone fracture healing and treat osteoporosis. Aim of the study: Achieving peak bone mass by adolescence has now been accepted to be fundamental for preventing osteoporosis in adulthood life. This study investigated the possibility of increasing peak bone mass in young rats using the total flavonoid extract of Epimedium herb (TFE). Materials and methods: TFE was intragastrically administered to one-month-old Wistar rats at a low (100 mg/kg), middle (200 mg/kg) or high dose (400 mg/kg). Whole body bone mineral density (BMD) was measured by dual-energy X-ray absorptiometry every two weeks. When BMD of any one of TFE groups was found to be significantly higher than that of the control, all rats were sacrificed, serum samples were collected for bone turnover biochemical assays, and femurs, tibiae and vertebrae were isolated and used in BMD, mechanical, micro-structural, histomorphometric and mechanistic studies. Results: Administration of TFE at middle and high doses for two months significantly increased the whole body, femoral and vertebral BMDs, and improved the bone mechanical and micro-architectural properties. The serum turnover biochemical results and the enhanced expression levels of bone-formation regulatory genes (Runx-2, OSX, and BMP-2) demonstrated that TFE administration increased bone formation but had no effect on bone resorption. The increased phosphorylation levels in femurs of PKA and CREB and expression of AC10 (the only soluble form of adenylyl cyclase) and the increased serum cAMP level after 4 h of TFE administration indicated that TFE promoted bone formation by activating the AC10/cAMP/PKA/CREB pathway in vivo. Conclusions: Oral administration of TFE at 200 mg/kg for two months can increase the peak bone mass of growing rats, suggesting the possibility of using total flavonoid extract of Epimedium herb to increase the peak bone mass in adolescence which is important for preventing osteoporosis in adult life. Graphical abstract: